Children's education in secure custodial settings: Towards a global understanding of effective policy and practice. (April 2021) - ahmed Shafi, Adeela; Little, Ross; Case, Stephen
Abstract: This unique editorial paper is one of the first that discusses the education of incarcerated young people in an international education journal. We review the eleven papers in the Special Issue on children's education in secure custodial settings to provide key insights with the aim of moving towards a global understanding of what effective policy and practice may look like. In examining the range of cross-disciplinary papers from a range of different cultural contexts including the UK, Germany, UAE, US, Nigeria and South Africa, we are able to illuminate some of the commonalities in the education of young people who are incarcerated as well as some of the background characteristics – many of which are strikingly similar. We employed the ideas of the bio-socio-ecological systems model to explore the proximal and distal systems that interact to affect the educational experiences of the young people. These included at the microsystemic level the importance of relationships in engaging the young people with education and learning and that, the relationships between the key actors (mesosystem) as well as the importance of effective leadership (exosystem) were critical elements in improving the experience of education in custodial settings. But rather predictably, the structural disadvantages (macrosystem) that young people who come into contact with youth justice face and how these are not appropriately addressed that came into sharp focus, possibly because many countries take a punitive approach to youth offending. We argue that there are things that can be done at each systems level but that in order to make the changes to genuinely improve the lives of these young people, we make a bold call upon the global community (macrosystem), through the UNCRC to challenge themselves for a radical overhaul of youth justice approaches which put the child as child first and offender second in order to meet the commitment in Article 28.